MANAGEMENT OF SEPTIC SHOCK PATIENTS WITH INTRABDOMINAL TRAUMATICS IN THE INTENSIVE CARE UNIT - Putra, Indra Sukmana; Palinrungi, Ari Santri (Jurnal Kedokteran Mulawarman, 2024)
Management of patients with septic shock with intrabdominal trauma is a complex medical treatment in the intensive care unit because the patient must be closely monitored and given adequate therapy. This case report is a case from the intensive care unit at Wahidin Sudirohusodo Hospital, Makassar. The patient was treated for 30 days starting on 10/24/23. The patient is a 15 year old male with the main complaint of a stab wound from a wooden beam that was stuck in his buttocks after falling from an 8 meter high building. The patient suffered stab wounds from the rectal, intrabdominal, diaphragm, left hemithorax to the pericard. The patient was referred from Pelamonia Hospital, Makassar, which had undergone airway treatment, then referred to Wahidin Hospital, Makassar. This patient underwent resuscitation and surgery, then was transferred to the intensive care unit. During the operation, serous laceration of the transverse colon, rectal laceration, urethral rupture, diaphragm and pericardial laceration were found. Patients had an APACHE II score of 17, SOFA score of 6 predicted mortality of 33.3%. Management during in the intensive care unit is treating the source of infection, fluid resuscitation, administering vasopressors. Norepinephrine as a first-line vasopressor agent with an initial target mean arterial pressure (MAP) is > 65mm Hg. Vasopressin is the second choice for treating septic shock, targeting MAP ≥ 65mmHg. Complicated intrabdominal infections are often caused by polymicrobial infections and require a combination of parenteral antibiotics during treatment. Therefore, it is necessary to select an antimicrobial agent appropriate to the patient's individual dosage. In cases of suspected intrabdominal infection, an aminoglycoside in combination with a beta lactam is recommended once daily, as gram-negative multidrug resistance often occurs. The empirical antibiotic given was a combination of meropenem 1gr/8 hours/IV + Amikacin 1gr/24 hours/IV for 6 days, continuous renal replacement therapy on treatment days 2 to 3 for 24 hours with CVVDHF modality. The results of the procalcitonin examination showed a downward trend followed by improvement in hemodynamics, decreased need for vasopressors, improved consciousness, gradual removal of the ventilator and transition to usual care on day 20. Comprehensive sepsis management resulted in better patient outcomes.Key words: Septic shock, Intrabdominal infection, Resuscitation, Continuous renal replacement therapy.